2021
DOI: 10.3389/fmars.2021.685282
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction Under Stress: Acute Effect of Low Salinities and Heat Waves on Reproductive Cycle of Four Ecologically and Commercially Important Bivalves

Abstract: The impacts of climate change on the structure and functioning of estuaries is a major focus of concern, even more when the affected species support important fisheries as the bivalves Ruditapes decussatus, Ruditapes philippinarum, Venerupis corrugata, and Cerastoderma edule in Europe. Their reproductive performance, in the context of climate stressors, had not been investigated so far. Our objective was to experimentally evaluate acute stress effects over gonad development after 6 days of low salinity stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 92 publications
1
32
2
Order By: Relevance
“…Fishers also demonstrated strong local environmental knowledge and awareness about the impacts of climate change on their activity, which is also consistent with previous research (Shaffrill et al, 2017;Pita et al, 2020). Our findings also showed that all fishers agreed with the expert opinion (Peteiro et al, 2018;Domıńguez et al, 2020;Domıńguez et al, 2021;Vaźquez et al, 2021) about the new scenarios of climate change for the future of shellfish, and noted that these scenarios would be negative for their activity.…”
Section: Considering Local Fishers Knowledge Helps To Disentangle Soc...supporting
confidence: 91%
See 4 more Smart Citations
“…Fishers also demonstrated strong local environmental knowledge and awareness about the impacts of climate change on their activity, which is also consistent with previous research (Shaffrill et al, 2017;Pita et al, 2020). Our findings also showed that all fishers agreed with the expert opinion (Peteiro et al, 2018;Domıńguez et al, 2020;Domıńguez et al, 2021;Vaźquez et al, 2021) about the new scenarios of climate change for the future of shellfish, and noted that these scenarios would be negative for their activity.…”
Section: Considering Local Fishers Knowledge Helps To Disentangle Soc...supporting
confidence: 91%
“…-Part C (Climate change impacts and future scenarios): the interviewees were asked their opinion about predictions, suggesting that abundance of shellfisheries (except the Manila clam) will decrease in the near future (Domıńguez et al, 2020;Domıńguez et al, 2021;Vaźquez et al, 2021), and what fishers would do if these predictions come true;…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations